Design a filter for harmonics caused by non-linear load and resonance coused by power factor correction capacitor - Adan, Nor Faezah (2016)
The traditional approach to power factor correction (PFC) in industrial applications involves installation of power factor correction capacitor banks (PFCC). However, with the expanding use of non-linear equipment such as adjustable speed drives (ASDs), power converters etc., power factor (PF) improvement has become difficult due to the presence of harmonics generated by the non-linear equipment. The resulting capacitive impedance of the PFCC may form a resonant circuit with the source inductive reactance at a certain frequency, which is likely to coincide with one of the harmonic frequency of the load. This condition will trigger large oscillatory currents and voltages that may stress the insulation and cause subsequent damage to the PFCC and equipment connected to the power system (PS). Besides that, high PF cannot be achieved due to power distortion. These have imposed the need for an approach to PFC by addressing the harmonics problem. This project analyzes both passive filter and shunt active power filter (SAPF) techniques to mitigate resonance and overall harmonics in the PS through simulation using PSCAD software. A test case is presented to demonstrate the applicability of the proposed techniques for harmonics reduction and PFC at the same time. The implementation of SAPF together with passive filter have resulted in significant improvement on both total harmonic distortion for voltage (THDV) and total demand distortion for current (TDDI) with maximum values of only 2.93% and 9.84% respectively which are within the IEEE 519-2014 standard limits. In terms of PF improvement, the combined filters have excellently achieved the desired PF, 0.95 for firing angle, α values up to 40°.